Uma fenomenologia do sofrimento espiritual: contribuições da antropologia fenomenológica de Edith Stein - Mendes, Lucas Oliveira (2024)
The present research addresses the complexity of spiritual suffering as an intrinsically human phenomenon that imposes itself upon existence and becomes inevitable. At times, suffering is taken as synonymous with sadness, discouragement, illness, among other emotions and feelings. The ambiguity of interpretations about human existence and its essential characteristics has grown in the scientific and social realms in times of profound suffering and existential emptiness. Therefore, the development of a phenomenology of spiritual suffering based on the phenomenological anthropology of Edith Stein (1891-1942) was fundamental to highlight the need for a clear understanding of the concept of suffering, confronting the growing conceptual distortion and, consequently, the practice that arises amid positivist, materialist, and reductionist approaches present in Philosophy, Psychology, and other sciences dedicated to studying issues related to human beings. Guided by the phenomenological method, the proposal aims to distinguish and define key concepts, such as human being, physical suffering [pain], psychic suffering [psychic disturbance], and spiritual suffering [human suffering]. Careful bibliographic analyses were conducted, as well as a dynamic exploration of texts and examples related to the theme of suffering from other authors such as Viktor Frankl (1905-1997) and Constantin Noica (1909-1987). The biographical and bibliographical review of Edith Stein was important to demonstrate her personal experiences in the experience of suffering. The assimilation of Edmund Husserl's (1859-1938) phenomenology by Stein and her pedagogical and detailed description of the physical, psychic, and spiritual dimensions of the human person provided an in-depth understanding based on the phenomenology of the structure of the Human Person. It was demonstrated that the human being is endowed with freedom and will, so their free acts arise from motivations and are not confined to the determination of psychic causality or any other type of conditioning and determination. The study concludes that suffering, originating from the specific dimension of the human person, the spiritual dimension, unveiled in its eidos, is suffering in itself, properly human, referred to as spiritual suffering. Such suffering may be motivated by moral, existential, or religious issues. The examples of the origin of each type of suffering were demonstrated in the literature of Dostoevsky (1821-1881), Tolstoy (1828-1910), Saint John of the Cross (1542-1591), Saint Teresa of Avila (1515-1582), and the biblical character Job. However, although suffering is originally spiritual, it can reach psychic and physical dimensions, and it can also originate in the spirit following an experience of pain and/or psychic disturbance. This occurs due to the interconnection of the structure of the human person, which is not fragmented and does not accept reductionism regarding what is human. The very division of body, soul, and spirit, elaborated by Stein, is a methodological and pedagogical function for a better understanding of the structure of the Human Person. Finally, the phenomenology developed in this work proves to be fundamental for all practical and theoretical care work for the suffering being because it is by knowing the face of suffering that one can care for those who suffer, and it is guided by meaning that one can overcome existential emptiness.